2015
DOI: 10.1038/srep18186
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure and function of Helicoverpa armigera sterol carrier protein-2, an important insecticidal target from the cotton bollworm

Abstract: The cotton bollworm, Helicoverpa armigera, has developed strong resistance to many insecticides. Sterol Carrier Protein-2 (SCP-2) is an important non-specific lipid transfer protein in insects and appears to be a potential new target. In order to elucidate the structure and function of Helicoverpa armigera SCP-2 (HaSCP-2), NMR spectroscopy, docking simulations, mutagenesis and bioassays were performed. HaSCP-2 composed of five α-helices and four stranded β-sheets. The folds of α-helices and β-sheets interacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…However, unlike mammals, insects and other arthropods cannot synthesize sterols de novo , and thus typically obtain them from food. Previous studies have demonstrated that interfering with dietary cholesterol usage delays insect growth and increases insect mortality …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike mammals, insects and other arthropods cannot synthesize sterols de novo , and thus typically obtain them from food. Previous studies have demonstrated that interfering with dietary cholesterol usage delays insect growth and increases insect mortality …”
Section: Introductionmentioning
confidence: 99%
“…This absorbing process includes two steps: (i) dietary cholesterol transportation through the apical membrane of enterocytes into cells, and (ii) intracellular cholesterol trafficking through the cytoplasm to the basal membrane where cholesterol is loaded into lipophorin . Sterol carrier protein‐2 (SCP‐2), a soluble protein abundant in enterocyte cytoplasm, has been shown to play an important role in the second step . Inhibitors targeting SCP‐2 significantly restricted dietary cholesterol trafficking, and showed high toxicity to insect pests and low toxicity to mammals that can synthesize their own cholesterol .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, single SCP-2 domain genes have also been proven to be expanded in mosquitoes [13]. Cholesterol is crucial for insects in order to grow, develop and reproduce, but they are not capable of synthesizing cholesterol de novo [14,15]. The mosquito SCP-2, Ae.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in vivo as well as in silico experiments have shown thiosemicarbazones as larvicides of A. aegypti . The structure and functional studies of other SCP2 proteins have also shown the insecticide specific affinity by several other small molecules. , …”
mentioning
confidence: 99%
“…10 The structure and functional studies of other SCP2 proteins have also shown the insecticide specific affinity by several other small molecules. 16,17 A. aegypti sterol carrier protein 2 (AeSCP2) and its isoforms are ∼13 kDa proteins, which share <35% sequence similarity among them and <15% with those of vertebrates. 6,18−21 The structural differences between the vertebrate and mosquito SCP2 revealed the absence of a short helical fragment between α-helix 1 and β-strand 1, suggesting its role in the insecticide specificity in mosquitoes.…”
mentioning
confidence: 99%